(untitled) (American Journal of Islam and Society, 2004)
Central to the conference, held during March 5-6, 2004, at Trinity College, University of Toronto (Canada), was the desire of its organizer, Andrew Hughes, to find analogies in other disciplines to his speculation that the European plainsong (liturgical chant) of the Middle Ages was performed in a manner similar to that of Middle Eastern music (“Continuous Music: Natural or Eastern? The Origins of Modern Performance Style”). His speculation stemmed from decades of discussions with his colleague Timothy McGee about the nature of musical sound. Oral transmission, its replacement by various difficult-to-interpret notations, and an often polemic rejection of Arabic influence make the investigation difficult and controversial.1 McGee responded (“Some Concerns about Eastern Influence in Medieval Music”) and later, working from practical experiments presented by a group of graduate students attending the conference, offered a very interesting new interpretation. Some reservations were expressed by Charles Burnett (Warburg Institute, London), a distinguished Arabist with musicological qualifications. He was invited to comment on the initial round table and the conference as a whole. Other papers relevant to music were George Sawa’s review of Arabic theories of medieval music (“The Uses of Arabic Language in Medieval Rhythmic Discourses”). He referred to numerous matters that might have a bearing on European music, especially with respect to ornamentation and rhythm. Art Levine discussed other non-western musical cultures, some of which were also influenced by Islamic music, and raised questions about ornamentation, tuning, and the nature of pitch (e.g., what is a note? “What Can Non-Western Music Offer?”). Moving from the sound of music to words about it, Randall Rosenfeld described numerous pilgrimage and Crusader chronicles. They contain passages reporting that Europeans found little strange in eastern music, suggesting that eastern and western music cannot have been as dissimilar as seems to be the case today (“Frankish Reports of Central Asian and Middle Eastern Musical Practice”). John Haines traced in detail the use of Arabic terms from Adelard of Bath’s twelfth-century translation of Euclid’s geometrical writings to an important mid-thirteenth-century musical treatise, where the terms for quadrilateral shapes resembling square notation are used to refer to musical symbols (“Anonymous IV’s Elmuahim and Elmuarifa”). Luisa Nardini presented details of particular melodic characteristics in Gregorian chants that identify Byzantine and Gallican melodies in Gregorian repertories (“Aliens in Disguise: Byzantine and Gallican Songs as Mass Propers in Italian Sources”). In other disciplines, Philip Slavin revealed the striking similarities of topics and words between Byzantine and Roman (Gregorian) penitential liturgy, seeing possible origins in Jewish prayers and the fourth-century Constitutiones Apostolorum (“Byzantine and Western Penitential Prayers ...